iNKT Cells Suppress Pathogenic NK1.1+CD8+ T Cells in DSS-Induced Colitis - Lee, Sung Won; Park, Hyun Jung; Cheon, Jae Hee; Wu, Lan; Van Kaer, Luc; Hong, Seokmann (Frontiers in Immunology, 2018)
T cells producing IFNγ play a pathogenic role in the development of inflammatory bowel disease (IBD). To investigate the functions of CD1d-dependent invariant natural killer T (iNKT) cells in experimental colitis induced in Yeti mice with dysregulated expression of IFNγ, we generated iNKT cell-deficient Yeti/CD1d KO mice and compared colitis among WT, CD1d KO, Yeti, and Yeti/CD1d KO mice following DSS treatment. We found that deficiency of iNKT cells exacerbated colitis and disease pathogenesis was mainly mediated by NK1.1+CD8+ T cells. Furthermore, the protective effects of iNKT cells correlated with up-regulation of regulatory T cells. Taken together, our results have demonstrated that CD1d-dependent iNKT cells and CD1d-independent NK1.1+CD8+ T cells reciprocally regulate the development of intestinal inflammatory responses mediated by IFNγ-dysregulation. These findings also identify NK1.1+CD8+ T cells as novel target cells for the development of therapeutics for human IBD.